A Very Low-Profile Dual Output LLC Resonant Converter for LCD/LED TV Applications - Demirel, Ibrahim; Erkmen, Burcu (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2014)
The concept of low-profile power supply becomes a current issue because of the recent trends in LCD/LED TV consumer market. Realizing a low-profile power supply with high power density is a challenging work due to the size limitation of passive components. In this paper, a very low-profile dual output LLC resonant converter proposed by considering the criteria of 10 mm component height limit without any drop-in cuts on the surface of printed circuit board. The simulation model of the converter is applied to the SPICE tool in order to estimate the performance and borders of the passive components. On the basis of theoretical approach and simulation results, two low-profile transformers are utilized in order to acquire a prototype with 200 W output power (24 V/6 A and 12 V/4.5 A). LLC series resonant converter prototype with the dimension of 140 mm x 291 mm x 10 mm achieves 89.4% efficiency at nominal load conditions. The input voltage range is between 330 to 400 V and the nominal input voltage is specified as 400 V. Operating frequencies are obtained as 65 and 81 KHz at 330 and 400 V, respectively, under the nominal load conditions. Thermal and electromagnetic interference performances of the proposed converter are included in the paper to validate experimental study.
Keywords: Dual Output; leakage reduction method; LLC resonant converter; low-profile power supply; DESIGN METHODOLOGY; VOLTAGE; FREQUENCY; Engineering